2015
DOI: 10.1111/1467-8551.12146
|View full text |Cite
|
Sign up to set email alerts
|

Voice, Affective Commitment and Citizenship Behavior in Teams: The Moderating Role of Neuroticism and Intrinsic Motivation

Abstract: This paper provides an empirical examination of the effects of co-workers' procedural justice, defined as the individual's perception of how procedural justice is displayed towards him/her by the group. Drawing on the social exchange literature, it is confirmed that team affective commitment mediates the relationship between team voice -a form of co-workers' procedural justice -and team citizenship behaviors. The study also tests whether this positive indirect effect is moderated by neuroticism and intrinsic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(53 citation statements)
references
References 111 publications
1
52
0
Order By: Relevance
“…Their study found a strong relationship among the three. Subsequent studies reaffirmed the notion that employee voice is a “state‐like” communication behavior that is dependent on individual traits as well as situational variables (LePine & Van Dyne, ; Ohana, ). Based on the above discussion, we argue that subordinates’ willingness to communicate, a trait‐like construct, is positively related to its state‐like form, “likelihood to voice” (see Saunders et al, ).
Hypothesis 1: Subordinates’ willingness to communicate is positively related to their likelihood to voice .
…”
Section: Theory and Hypothesesmentioning
confidence: 86%
“…Their study found a strong relationship among the three. Subsequent studies reaffirmed the notion that employee voice is a “state‐like” communication behavior that is dependent on individual traits as well as situational variables (LePine & Van Dyne, ; Ohana, ). Based on the above discussion, we argue that subordinates’ willingness to communicate, a trait‐like construct, is positively related to its state‐like form, “likelihood to voice” (see Saunders et al, ).
Hypothesis 1: Subordinates’ willingness to communicate is positively related to their likelihood to voice .
…”
Section: Theory and Hypothesesmentioning
confidence: 86%
“…A further group of participants believed voice was mostly exerted on behalf of the value of organizational citizenship (Detert and Burris, 2007;Ohana, 2016), perceiving speaking up as an organizational good. A further group of participants believed voice was mostly exerted on behalf of the value of organizational citizenship (Detert and Burris, 2007;Ohana, 2016), perceiving speaking up as an organizational good.…”
Section: (23) Tensions Of Organizing and Performingmentioning
confidence: 99%
“…Numerous studies attest to the importance of employee involvement in upward problem-solving within organizations as a mechanism for employee voice (see Mowbray et al, 2015;Wilkinson, Townsend, Graham, & Muurlink, 2015 for recent reviews). Janssen and Gao (2015) found among 337 supervisor-subordinate dyads in the Chinese manufacturing industry that when employees perceive that they have high voice status, they are motivated to engage in subsequent voice behavior (see also Ohana, 2016). Employee voice can also be an important component of psychological safety in the workplace because it provides employees with a safe climate (Milliken et al, 2015).…”
Section: Linking Employee Voice Mechanisms and Lgbt Expatriationmentioning
confidence: 99%